2021
DOI: 10.1016/j.vas.2020.100155
|View full text |Cite
|
Sign up to set email alerts
|

Corticosterone in feathers: Inter- and intraindividual variation in pullets and the importance of the feather type

Abstract: Measuring corticosterone concentrations in feathers of poultry may be suitable to determine birds' exposure to stress. It is thinkable, that in laying hens such information could be helpful as an animal welfare indicator to evaluate adverse husbandry conditions and to predict the risk of developing behavioral disorders, such as feather pecking and cannibalism. Yet, there are some fundamental issues which remain unclear. Therefore, the objective of the current pilot study was to examine the inter- and intraindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…Even though the FCORT concentrations of secondary 1 and 3 were significantly different within the studied lines, we found that the inter-individual variation in FCORT was larger than the intra-individual variation when looking at both periods (53-56% vs. 29%). This is contrary to what was found in chickens by Häffelin et al [23], who found that intra-individual variation was higher than the variation between birds. However, they analyzed many more feather types (scapular, tail, wing, e.tc.)…”
Section: Fcort Variabilitycontrasting
confidence: 99%
See 4 more Smart Citations
“…Even though the FCORT concentrations of secondary 1 and 3 were significantly different within the studied lines, we found that the inter-individual variation in FCORT was larger than the intra-individual variation when looking at both periods (53-56% vs. 29%). This is contrary to what was found in chickens by Häffelin et al [23], who found that intra-individual variation was higher than the variation between birds. However, they analyzed many more feather types (scapular, tail, wing, e.tc.)…”
Section: Fcort Variabilitycontrasting
confidence: 99%
“…This may explain why, in the present study, the intra-individual variation (32%) is slightly greater than the variation between individuals (25-30%) during the pre-lay period since this is supposed to reflect levels of FCORT before egg production. Inter-individual variation is an important consideration when assessing how individuals respond to the same situation [23]. Our results indicate more variability in the FCORT response between birds than within birds during energetically demanding periods, which may relate to differences found between genetic lines.…”
Section: Fcort Variabilitymentioning
confidence: 69%
See 3 more Smart Citations